Assessment of Cell–Material Interactions in Three Dimensions through Dispersed Coaggregation of Microsized Biomaterials into Tissue Spheroids. Issue 29 (26th June 2022) - Fois, Maria G.; Tahmasebi Birgani, Zeinab N.; Guttenplan, Alexander P. M.; Blitterswijk, Clemens A. van; Giselbrecht, Stefan; Habibović, Pamela; Truckenmüller, Roman K.
Abstract: In biomaterials R&D, conventional monolayer cell culture on flat/planar material samples, such as films, is still commonly employed at early stages of the assessment of interactions of cells with candidate materials considered for a biomedical application. In this feasibility study, an approach for the assessment of 3D cell–material interactions through dispersed coaggregation of microparticles from biomaterials into tissue spheroids is presented. Biomaterial microparticles can be created comparatively quickly and easily, allow the miniaturization of the assessment platform, and enable an unhindered remodeling of the dynamic cell–biomaterial system at any time. The aggregation of the microsized biomaterials and the cells is supported by low‐attachment round‐bottom microwells from thin polymer films arranged in densely packed arrays. The study is conducted by the example of MG63 osteoblast‐like and human mesenchymal stem/stromal cells, and a small library of model microbiomaterials related to bone repair and regeneration. For the proof of concept, example interactions including cell adhesion to the material, the hybrid spheroids' morphology, size, and shape, material‐associated cell death, cell metabolic activity, cell proliferation, and (osteogenic) differentiation are investigated. The cells in the spheroids are shown to respond to differences in the microbiomaterials' properties, their amounts, and the duration of interaction with them. Abstract : An approach for the assessment of 3D cell–material interactions through dispersed coaggregation of biomaterial microparticles into tissue spheroids in microwell arrays is presented. The micromaterials allow an unhindered remodeling of the dynamic cell–biomaterial system. The cells in the hybrid spheroids are shown to respond to differences in the microbiomaterials' properties, their amounts, and the duration of interaction with them.